Stock status of Nile tilapia (Oreochromis niloticus) in Aneuk Laot Lake, Sabang District, Aceh Province, Indonesia - Eko Prianto; Rudi Masuswo Purwoko; Kamaluddin Kasim (Society for Indonesian Biodiversity, 2021)
Abstract. Prianto E, Purwoko RM, Kasim K. 2021. Stock status of Nile tilapia (Oreochromis niloticus) in Aneuk Laot Lake, Sabang District, Aceh Province, Indonesia. Biodiversitas 22: 3364-3370. The Nile tilapia (Oreochromis niloticus) fishery in Aneuk Laot Lake plays a vital role in the local livelihoods. There is an indication of the massive exploitation of the species that potentially harm the stock and threaten its sustainability. This research aims to evaluate and assess the Nile Tilapia's stock status and use the results as baseline information to the management authorities. Surveys were conducted from May 2018 to April 2019 by collecting the length-weight data, sex, and gonadal maturity stage of 600 individuals. The Length-Based Spawning Potential Ratio (LB-SPR) was used to determine the Spawning Potential Ratio (SPR) and compared the results to the reference point. The results show that 50% of the females have matured at 15.1 cm, while the males at 17.8 cm. The individual fish length varies from 12.15 to 20.5 cm, whereas 50% of them were caught at size 17.8 cm (Lc50), meaning that predominantly of the fish had experienced first spawning before they were captured. The current SPR is about 5%, confirming the Nile tilapia's stock status is at an unhealthy state. Consequently, the precautionary approach, such as increasing the mesh size and limiting effort, should be considered to ensure the sustainability of the recruitment.